Improving fuel statistics for Danish aviation - Winther, Morten (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
In Denmark there is a growing need for consistent aviation fuel use statistics in order to meet specific requirements from different statistical bodies, to support emission inventories asked for by international conventions and for environmental monitoring work according to national target plans. In the Danish energy statistics fuel used by flights from Denmark to Greenland and the Faroe Islands are reported as international fuel use, while the United Nations Framework Convention on Climate Changes (UNFCCC) prescribe this fuel use to be reported as a part of the Danish domestic fuel use together with the fuel used in Greenland and the Faroe Islands for domestic flying. This project aim to: 1) develop a method to divide total aviation fuel sold in Denmark into domestic and international aviation fuel sale figures from 1985 to 2000, and 2) estimate the fuel used by flights from Denmark to Greenland and the Faroe Islands, respectively and domestic flights inside Greenland and the Faroe Islands, and 3) develop a method which allocates domestic and international fuel use into figures for passenger and cargo. Both methods under 1) and 2) should be used in the future to ensure consistent fuel use statistics. This paper presents the results from this project.